Electrical characteristic of photovoltaic thermal collector with water-multiwalled carbon nanotube nanofluid flow - Nur Farhana Mohd Razali; Ahmad Fudholi; Mohd Hafidz Ruslan; Kamaruzzaman Sopian (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Photovoltaic thermal (PVT) studies show promising results from utilizing waste heat under the PV module. Heat removal is essentially the base of a PVT collector. The heat absorption from the back of the PV module used for different purposes. Solar energy being collected are mostly turned into heat and needs to be extracted to maintain PV’s efficiency. The PVT collector works similar to a flat plate solar collector, except that the short wavelengths are converted into electricity and the remaining wavelengths into useful heat. The heat collected is also at a lower magnitude than collected by solar thermal collectors. This study present the experimental investigation to improve the efficiency of PVT collector with and without Multiwalled Carbon Nanotube (MWCNT) nanofluid using spiral rectangular tube absorber as cooling. The electrical characteristic of PVT collector are represented by plotting power (P)-voltage (V), current (I)-voltage (V) curves. The results shows the power generated will increase with the increasing of solar radiation, and efficiency is slightly higher than the PVT collector without MWCNT. In addition, the highest maximum power increase is obtained when the 0.1 wt% MWCNT nanofluid is used as a coolant in the PVT collector.